Assessment of measurable residual disease after induction chemotherapy in acute lymphoblastic leukemia patients in a tertiary care hospital - Rahman, M. Aminur; Ahmed, Munim Ahmed; Akter, Soniya; Nasrin, Papri; Islam, Ismat A.; Akhter, Nasrin; R. Kabir, M. Maruf; Poddar, Sharup C.; H. Masud, M. Adnan; Shah, M. Salahuddin (International Journal of Advances in Medicine, 2024)
Background: Measurable residual disease (MRD) is a crucial prognostic factor in acute lymphoblastic leukemia (ALL), influencing treatment outcomes and long-term survival. This study investigates the prevalence of MRD post-induction chemotherapy and its association with clinical, demographic, and biochemical markers in ALL patients at a tertiary care hospital. Methods: This observational cross-sectional study was conducted at Bangabandhu Sheikh Mujib Medical University, Dhaka, Bangladesh, from August 2021 to July 2022. A total of 22 newly diagnosed ALL patients underwent induction chemotherapy and MRD evaluation using flow cytometry. Clinical signs, demographic data, and laboratory findings, including serum creatinine, uric acid, and BCR-ABL1 status, were recorded. Statistical analyses assessed the relationships between MRD status and various predictors. Results: Of the 22 patients, 7 (31.82%) remained MRD positive after induction chemotherapy. Anaemia was prevalent, affecting 20 participants (90.91%). MRD positive patients had higher serum creatinine (mean 1.23±0.31 mg/dl) and uric acid levels (mean 7.09±1.62 mg/dl) compared to MRD negative patients. None of the MRD positive patients tested positive for BCR-ABL1. Six of the 7 MRD positive patients were male (85.71%). Bone marrow analysis showed 5 MRD positive patients (71.43%) achieved complete remission. Risk stratification did not significantly correlate with MRD status. Conclusions: MRD is a critical prognostic tool in ALL management, correlating with higher biochemical markers of tumor burden and a distinct clinical profile. These findings support integrating MRD assessment with detailed clinical and laboratory evaluations to refine treatment strategies and improve patient outcomes in ALL.